Effect of Intense Weathering and Postdepositional Degradation of Organic Matter on Hg/TOC Proxy in Organic‐rich Sediments and its Implicationsfor Deep‐Time Investigations - Guillaume Charbonnier; Thierry Adatte; Karl B. Föllmi; Guillaume Suan (Geochemistry, Geophysics, Geosystems, 2020)
Abstract Mercury (Hg) enrichments in sediments are increasingly used as tracer for distal volcanism in deep‐time investigations. The impact of changes in organic‐matter deposition and preservation on sedimentary Hg sequestration is, however, poorly understood. In this study, we evaluate the potential role of intense weathering and postdepositional organic‐matter degradation on the Hg/TOC proxy in sediments. For this, we investigate weathering profiles in organic‐rich sediments from lowermost Toarcian sediments (T‐OAE; Lafarge cement quarry, France) and organic‐rich deposits from the uppermost Cenomanian‐lowermost Turonian Bonarelli level (OAE2; Furlo and Monte Velo, Italy; Manilva and El Chorro, Spain). The comparison of Hg data along weathering profiles in lowermost Toarcian sediments indicates that recent intense oxidation of the originally organic‐rich deposits has removed up to 89% of the Hg signal. The organic‐rich sediments of the Furlo and Manilva sections are characterized by lower Hg/total organic carbon (TOC) ratios, which suggest important Hg scavenging by organic matter (OM) deposition. At the opposite, in equivalent successions, three significant positive Hg/TOC excursions persist at El Chorro and Monte Velo. These samples exhibit low Hydrogen Index (HI) values, which plot in the field of type‐III OM. This resulted from postdepositional degradation of marine OM type II to type III, which largely modified the amount and the quality of OM. Consequently, the recorded Hg/TOC ratios do not reflect original Hg drawdown but postdepositional oxidation, suggesting that extreme care is needed in the evaluation of the history of OM preservation when using Hg as a proxy for volcanic activity.